2018
DOI: 10.1590/1806-9282.64.09.770
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for hypofractionated whole-breast irradiation

Abstract: This recommendation consensus for hypofractionated whole-breast radiotherapy (RT) was organized by the Brazilian Society of Radiotherapy (SBRT) considering the optimal scenario for indication and safety in the technology applied. All controversies and contraindication matters (hypofractionated RT in patients who underwent chemotherapy [CT], hypofractionated RT in lymphatic drainage, hypofractionated RT after mastectomy with or without immediate reconstruction, boost during surgery, hypofractionated RT in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Of them, 168 publications were found duplicated and 7205 did not meet the selection criteria. A total of 59 documents (43 CPGs [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ] and 16 CSs 42–57 [ [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ]) were identified for final evaluation ( Table 1 ). The flow diagram detailing the study selection process is provided in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of them, 168 publications were found duplicated and 7205 did not meet the selection criteria. A total of 59 documents (43 CPGs [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] ] and 16 CSs 42–57 [ [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ]) were identified for final evaluation ( Table 1 ). The flow diagram detailing the study selection process is provided in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In domain 5 (applicability) only 1 (2%) CPG scored >75%. Domain 6 (Editorial independence) related to the bias linked to conflict of interest, scored >75% in 34 (58%) CPGs but it was 0% or almost 0% in five CPGs [ 26 , 40 , 57 , 63 , 64 , 66 ] and four CSs [ 72 , 75 , 76 , 78 , 82 ]. The ASCO [ [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , 52 , 53 ], Dutch [ 31 ] and Colombian [ 58 ] CPGs had the highest quality scores ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The local control was similar among different ages [9,15,24]. There was NO agreement regarding the safety of indication of hypofractionated RT of exclusively the breast for patients with age under 40 years [12].…”
Section: IVmentioning
confidence: 71%
“…The conventional fractionation (1.8-2 Gy per fraction) has been used as the standard over the last decades, with a total dose of 50-50.4 Gy over 25-28 sections, distributed over 5 consecutive weeks [12]. The use of small fractions (≤2•0 Gy) in curative radiotherapy is strongly based on reliable data for squamous carcinomas of the bronchus, cervix uteri, and head and neck ,which show that these tumors are much less sensitive than lateresponding healthy tissues to the size of individual fractions.…”
Section: Radiobiological Backgroundmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In the curative setting of breast and prostate cancer, both among the most common cancers and often requiring radiotherapy 8,9 , a strong body of evidence supporting hypofractionation has informed professional society guidelines. [10][11][12] Within prostate cancer, three non-inferiority trials with over 30,000 combined patient-years of follow-up found that moderate hypofractionation was noninferior to conventionally fractionated treatment for 5-year biochemical or clinical failure. [5][6][7] In breast cancer, large Canadian and United Kingdom trials have shown no difference between conventional and hypofractionated treatment in local recurrence, overall survival, or cosmetic outcome at 10 years.…”
Section: Introductionmentioning
confidence: 99%